دور هيئة الشرعية الوطنية في الرقابة الشرعية على المصارف الإسلامية في إندونيسيا ومنهجها في الفتوى: دراسة وصفية تحليلة نقدية - Hatta Syamsuddin; Abdul Khaliq Hasan; Moh Muinudinillah (IAIN Surakarta, 2016)
The emergence of Islamic banking was considered as a response to the desire of Muslim communities to disassociate from usury (riba based) system. The development of time increasing the diversity of financial transactions, both in trading and banking business, which has no provisions in the old sources of Islamic jurisprudence. This dangerous phenomenon was the reason for the importance of a Sharia Supervisory Board to ensure all of banking transactions comply with the rules and principles of sharia. This research focused on the role of National Sharia Board and his methodology in fatwa. This research uses analytical descriptive methodology. The limitations of this research were about: how the National Sharia Board played their roles in Indonesia and how the method applied by the National Sharia Board in issuing a fatwa. The research found that: the National Sharia Board in Indonesia has played their roles, especially in developing Islamic finance industry, ensuring financial and banking transaction comply with the rules and principles of sharia, and providing awareness and guidance to the Muslim communities. The issuing of fatwa on financial transactions was the authority of the National Sharia Board. The National Sharia Board hold on procedures, specific steps, and certain agreed methodology in issuing fatwa. Nevertheless, there still some fatwas that caused controversy in the Islamic community.